Physics’ insights into pedestrian motion and crowd dynamics - Miguel, A. F. (2013)
Pedestrians’ world is not a static one, but rather one which is constantly in flux. The pedestrian dynamics is subject to a wide range of influences and displays an interesting phenomenology. Along with collective self-organization phenomena (e.g., streams of people, rivers of people, collective synchronization), there are also a multitude of applications in the context of crowd management, design of pedestrian facilities and urban planning.